Representing Identity of Nation and Post Modern Concern in the Shadow Lines: Exploring Identity and Patriotism in Amitav Ghosh's The Shadow Lines (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Indian writing in English has stepped its enormity by stirring up tradition and modernity in the production of workmanship. The enthusiasm for writing lit the consuming thirst of the essayists which turned their energy and technique to innovate new structures and styles of composing. Amitav Ghosh is one among the postmodernists. He is massively influenced by the political and social milieu of post free India. Being a social anthropologist and having the chance of visiting outsider grounds, he remarks on the present situation. The present paper is expected to look at Amitav Ghosh‟ treatment of the hazardous of identity in The Shadow Lines (1988), which as a memory novel, outlines couple of authentic occasions like the freedom development in Bengal, the Second World War and the Partition of India in 1947 and the communal uproars in Bangladesh and India. In this novel, Ghosh problematizes patriotism as he continued looking for identity.